Identification of Potential Pathogen Bacteria Causing Tuber Rot in Porang (Amorphophallus muelleri Blume) - Afifah Nur Aini; Rodiyati Azrianingsih; Irfan Mustafa (Journal of Tropical Life Science, 2020)
Tuber rot has been reported as one of the limiting factors to porang (Amorphophallus muelleri Blume) tuber production. Bacterial infection is one of the main causes of tuber rot during storage. In this study, a total of seven bacterial isolates obtained from porang tubers were tested for their potency to cause rotting on porang tubers. Porang tubers were immersed in bacterial suspension and incubated for 14 days. The physical properties of the tubers such as texture and color, and the chemical properties such as reducing sugar and ethanol content were determined at the end of incubation period. All infected tubers were soft, slimy and darker. Two isolates, T4 and T9A, had the highest potency to cause tuber rot indicated by the significantly higher reducing sugar content (14.38 and 15.32 mg/ml) and higher ethanol content (32.17 and 35.05%) compared to control tubers which were not infected with bacteria. Both isolates were identified as Bacillus altitudinis and Pseudomonas stutzeri, respectively, based on 16S rDNA sequence analysis.